The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/nar/gkx631
|View full text |Cite
|
Sign up to set email alerts
|

SupeRNAlign: a new tool for flexible superposition of homologous RNA structures and inference of accurate structure-based sequence alignments

Abstract: RNA has been found to play an ever-increasing role in a variety of biological processes. The function of most non-coding RNA molecules depends on their structure. Comparing and classifying macromolecular 3D structures is of crucial importance for structure-based function inference and it is used in the characterization of functional motifs and in structure prediction by comparative modeling. However, compared to the numerous methods for protein structure superposition, there are few tools dedicated to the supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Some algorithms were developed to deal with flexibility by breaking the structures into smaller units that are superimposed independently, for example, in FATCAT for proteins 14 and SupeRNAlign for RNA. 15 Another approach involves the shifting of the level of comparisons from the entire structures to the individual structural elements, usually down to the level of the local environment of individual residues, which does not require superposition of structures, for example, in QCS, SphereGrinder, CAD‐score, LDDT, RPF and INF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some algorithms were developed to deal with flexibility by breaking the structures into smaller units that are superimposed independently, for example, in FATCAT for proteins 14 and SupeRNAlign for RNA. 15 Another approach involves the shifting of the level of comparisons from the entire structures to the individual structural elements, usually down to the level of the local environment of individual residues, which does not require superposition of structures, for example, in QCS, SphereGrinder, CAD‐score, LDDT, RPF and INF.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the measures of structural similarity listed above have been developed for comparing relatively rigid structures, they require superposition of these structures, and they are not easily applicable for the comparison of molecules that exhibit significant flexibility. Some algorithms were developed to deal with flexibility by breaking the structures into smaller units that are superimposed independently, for example, in FATCAT for proteins 14 and SupeRNAlign for RNA 15 . Another approach involves the shifting of the level of comparisons from the entire structures to the individual structural elements, usually down to the level of the local environment of individual residues, which does not require superposition of structures, for example, in QCS, SphereGrinder, CAD‐score, LDDT, RPF and INF.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there exist a wide number of different tools for the pairwise superposition of RNA 3D structures, which can be divided into two main groups based on the specific purpose they were developed to fulfill. The majority of the tools focus on producing a structure-based RNA sequence alignment [42][43][44][45][46][47][48][49] and therefore usually require single RNA chains as input [43,44,47]. Another large group of tools is focused on local tertiary motifs superposition and search [50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…CLICK is a topology-independent tool comparing of 3D structures without a scoring function measuring the structural similarity [18, 19]. Similar to SARA-Coffee [20] coupling with sequence alignments, SupeRNAlign iteratively superimposes the RNA fragment structures with R3D and maximizes the local fit [21]. They found that R3D is scoring the best among the tools without ESA-RNA in benchmark.…”
Section: Introductionmentioning
confidence: 99%